Impact of Accounting Information Systems of Cash Executions on Internal Controls of Company - Ambarwati, Rina; Gumilang, Andika Mugi; Rosidawaty, Rosidawaty; Sugiyono, Sugiyono; Chyntia, Ingkak; Aminudin, Dindin; Dadang, Dadang; Ulinnuha, Nor Fatah; Ramadhan, Muhammad dhitya (Formosa Journal of Multidisciplinary Research, 2024)
The study investigates how the accounting information system of cash expenditure affects the internal controls of the company. Cash expenditure, which is vital to business operations, is managed by accounting information systems (AIS). It is expected that effective use of AIS will improve the accuracy of transaction recording, reduce errors, and prevent fraud. The study uses a quantitative method by sending questionnaires to various that have implemented cash expenditure. The results show that there is a significant correlation between how well AIS manages cash expenditure and how well the company's internal controls. Good AIS implementation ensures that all transactions are properly recorded, authorizations are carried out according to procedures, and authorities can only access financial information. In addition, an integrated AIS offers audit trails that facilitate the tracking and verification of transactions by both internal and external auditors. These findings suggest that the use of effective cash expenditure can strengthen internal control mechanisms, improve financial integrity, and give confidence to stakeholders of the company's interests.